Neonatal outcome in early term and late term pregnancy - Gupta, Garima; Dwivedi, Seema; Agarwal, Rijul; Rajput, Anand; Sharma, Karishma; Dwivedi, Divya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Full-term neonates born between 37- and 41-weeks’ gestational age have been considered a homogeneous, low-risk group. However, recent evidence from studies has pointed toward increased NICU admissions and morbidity associated with births (37-38 weeks) compared with term neonates (39-41 weeks). The objective of this study was to compare the short-term morbidity of early-term vs term neonates in a county-based birth cohort using the primary objective of admission to a neonatal intensive care unit (NICU) or neonatology service. Methods: Retrospective observational population-based 2 year birth cohort study at Department of Obstetrics and Gynecology GSVM Medical College, Kanpur. All full-term live births comprised the birth cohort; this information was obtained from the hospitals’ perinatal databases, and data pertaining to NICU, or neonatology service admissions were extracted from individual medical records. Gestational age of early term (37 0/7-38 6/7 weeks) verses term (39 0/7-4 10/7 weeks). Admission to the NICU or neonatology service. Results: There were 17,132 live births during the 2 year period, of which 13679 had a gestational age between 37 and 41 weeks. Of all live births, 6204 (45.3%) were early term. Compared with term infants, early-term neonates had significantly higher risks for the following: hypoglycaemia (29.9% verses 14.7%), NICU or neonatology service admission (20.9% vs12.05 %), need for respiratory support (36.8% verses 29.9%), treatment with intravenous antibiotics [39.4% verses 25. Delivery by caesarean section was common among early-term births (45.9%)]. Conclusions: Early-term births are associated with high neonatal morbidity and with NICU or neonatology service admission. Evaluation of local prevalence data will assist in implementation of specific preventive measures and plans, as well as prioritize limited health care resources.